PERANAN RELIGIUSITAS DAN PREFERENSI RESIKO TERHADAP AKSES KEPADA LEMBAGA KEUANGAN MIKRO - ALFI SYUKRI RAMA (Universitas Islam Negeri Imam Bonjol Padang, 2016)
The research design is to create a framework where risk preferences and religiosity (Islam) borrowers in microfinance institutions (MFIs) can be estimated. Specifically, this study highlights the different characteristics of conventional microfinance borrowers (LKMK) and sharia (LKMS). Although much of the literature discussing the topic of conventional microfinance and Islamic finance individually, but still rare studies that discuss the characteristics of the borrower to choose only between these two financial institutions. Theories about Islamic microfinance is inherently suggests that financial institutions will be interesting for people who avoid risk (risk-averter), not a lover of risk (risk-lover). In addition, because of Islamic microfinance contracts do not charge interest on loans and the appeal of Islamic financial basis will be preferred by individuals who are relatively religious. The study was conducted by taking a sample of 30 primary data in the form of debtor LKMK and 29 debtors LKMS. The process of collecting data using questionnaires containing questions about basic demographics, besides the question that aims to bring risk preferences and Islamic religiosity. In the first stage, the study established several indices to measure risk preferences and religiosity using component analysis (Principal Component Analysis). At a later stage, to investigate the initial hypothesis, linear probability models used. The main findings estimate reflects the fact that appropriate initial hypothesis. Turns on LKMS customer financing is relatively more religious. Additionally, through the use of instruments on the game field experiments to uncover risk preferences, there is a fact that is little different from the initial hypothesis. Both types of customers have the same risk preference, they both love risk (risk-lovers) but customer financing at LKMS have a relatively lower level.